Smart geospatial practices and applications in local government : an altogether different language - Holdstock, David A. (Boca Raton, FL : CRC Press, 2020)
"This book is the guide that details best GIS applications and practices for the 34 departments in local government that can, and should, use GIS technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Local government -- Data processing; Local government -- Geographic information systems; Public administration -- Data processing; Public administration -- Geographic information systems; BUSINESS & ECONOMICS / Government & Business; LAW / Environmental; TECHNOLOGY / Environmental Engineering & Technology